UTILIZATION RATE FACILITIES OF TEMPAT PENDARATAN IKAN (FISH LANDI PLACE) AT SUNGAI RAYA DISTRICT OF KARIMUN, RIAU ISLANDS PROVINCE - Khairani Khairani; Alit Hindri Yani; Usman Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACTThis research was conducted in July 2017 offishingland place at Sungai Raya using survey method.Data analysis using technical analysis and facility utilization analysis.The facilities of fishing land place at Sungai Raya consist namelyprimary facilities, functional facilities, and supporting facilities. Of the 9 facilities in TPI Sungai Raya, 5 facilitiesutilizationwere calculated. The facility utilization rate in TPI Sungai Raya ranges from 0,3187% to 154,7967%. One facilities utilization rate were over its conditions optimal such as the area of the harbor pool,four facilities that have an optimal utilization rate are dock, depth of the harbor pool, fuel tank, fresh water tank, and ice factory. Keywords :fishing landplace, Kelurahan Sungai Raya, facilities utilization rate